Design of load frequency regulator for power systems subject to bounded persistent disturbance considering generation rate constraint - Kalvibool, Patipan; Arunsawatwong, Suchin (2015 54th Annual Conference of the Society of Instrument and Control Engineers of Japan (SICE), 2015)
This paper presents the design of load frequency regulator for power systems that are subject to persistent disturbance, in which all possible disturbances are treated as signals having uniform bounds on their magnitude and slope. The design objective is to determine a controller which maximizes the absolute value of the rate of change of the system's load (thereby maximizing the size of the possible set in some sense) while keeping the frequency deviation within its prescribed bound for all possible disturbances. In conjunction with the notion of conditionally linear model, the generation rate is required to stay within its linear range of operation for all possible disturbances. Consequently, the linear models of the systems are ensured to exist and, more importantly, theories for linear systems can be conveniently utilized. Using the known design framework consisting of the method of inequalities and the principle of matching, the design specifications are expressed as a set of distinct inequalities that can be solved in practice. The numerical results clearly illustrates the effectiveness and the usefulness of the framework adopted here.